Evaluation of Midwifery Care Standard Policy BPJS Health Participants - Astri Nurdiana; Ella Nurlailasari (Poltekkes Kemenkes Jakarta III, 2020)
Enforcement of national health insurance organized through Badan Penyelenggara Jaminan Kesehatan (BPJS) experiences various polemics, one of which relates to financing for midwifery care listed in Permenkes No. 52 of 2016 concerning health service fare standards in the health insurance program, whether the standard rate can cover the needs of services provided by midwives in rural or urban areas or not. The result found that there is no difference in midwifery care fare between urban and rural areas (p>0.05), but there are differences in midwifery care fare between rural and BPJS fare standard (p<0.05) and between urban fare and BPJS fare standard (p< 0.05)